2016
DOI: 10.5455/ijmsph.2016.22102015301
|View full text |Cite
|
Sign up to set email alerts
|

Iron status in sickle cell disorders

Abstract: Background: There is a general view that patients with sickle cell disease (SCD) reveal iron overload and that iron deficiency anemia is uncommon in them because of the availability of an adequate iron source from increased red cell turnover and blood transfusions. However, there are reports of iron deficiency in a proportion of these patients, which can often be missed because they exhibit already anemic condition. Objective: To evaluate the iron status and to determine the incidence of iron deficiency in sic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Similar opinion was given by Reynold et al [5] But the studies which are recently coming up show that the patients with sickle cell anaemia may be iron deficient. Patel et al [10] found that 4 In the same study, it was also found that 5 (11.62%) transfused patients and 14 (25%) non-transfused patients had decreased serum iron. Kassim et al [11] found that serum iron values were more in transfused patients as compared to non-transfused patients.…”
Section: Discussionmentioning
confidence: 81%
“…Similar opinion was given by Reynold et al [5] But the studies which are recently coming up show that the patients with sickle cell anaemia may be iron deficient. Patel et al [10] found that 4 In the same study, it was also found that 5 (11.62%) transfused patients and 14 (25%) non-transfused patients had decreased serum iron. Kassim et al [11] found that serum iron values were more in transfused patients as compared to non-transfused patients.…”
Section: Discussionmentioning
confidence: 81%